Strain Elastography - How To Do It? - Christoph F. Dietrich; Richard G. Barr; André Farrokh; Manjiri Dighe; Michael Hocke; Christian Jenssen; Yi Dong; Adrian Saftoiu; Roald Flesland Havre (Ultrasound International Open, 2017)
Tissue stiffness assessed by palpation for diagnosing pathology has been used for thousands of years. Ultrasound elastography has been developed more recently to display similar information on tissue stiffness as an image. There are two main types of ultrasound elastography, strain and shear wave. Strain elastography is a qualitative technique and provides information on the relative stiffness between one tissue and another. Shear wave elastography is a quantitative method and provides an estimated value of the tissue stiffness that can be expressed in either the shear wave speed through the tissues in meters/second, or converted to the Young’s modulus making some assumptions and expressed in kPa. Each technique has its advantages and disadvantages and they are often complimentary to each other in clinical practice. This article reviews the principles, technique, and interpretation of strain elastography in various organs. It describes how to optimize technique, while pitfalls and artifacts are also discussed.